Strategi Pengembangan Profesi Guru dalam Mewujudkan Suasana Pembelajaran yang Efektif - Muh Wajedi Ma'ruf; Riyo Asmin Syaifin (Al-Musannif, 2021)
This study aims to analyze teacher professional development strategies in creating an effective learning atmosphere by focusing on three sub-problems, namely: (1) The nature of effective learning; (2) various factors that influence the learning atmosphere; and (3) various strategies in teacher professional development as an effort to create an effective learning atmosphere. This type of research is library research. Data is collected from books, journals, or other scientific works regarding the theory of teacher strategies in realizing effective learning using documentation techniques and then analyzed using content analysis techniques. The results showed that learning was said to be effective if it fulfilled the learning objectives in a pleasant atmosphere for educators and students. There are two factors that influence the learning atmosphere, namely exogenous factors and endogenous factors. Various strategies for teacher professional development in creating an effective learning atmosphere through two development strategies, namely paradigm development and teacher competency development. This research has implications for the need for teachers to always carry out their duties professionally. The indicators of professionalism include always adhering to work ethics, independent (free from external pressure), fast (productive), precise (effective), efficient, innovative based on the principles of excellent service in accordance with the elements of science or systematic theory, professional authority, public recognition, and upholding the code of ethics.